Award for irrigation ideas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Irrigation Association (IA) has launched a competition for innovative irrigation ideas and technologies aimed at the world s smallholders. The winner receives US$ 10,000 (Euro 11,100) donated by Winrock International. Submit your proposal, no...